Beyond a Balanced View of Social Entrepreneurship within a Social-Commercial Dichotomy: Towards a Four-Dimensional Typology - Hein, Rüdiger (Sustainability, 2022)
With regard to the basic understanding of the location of social entrepreneurship, there is a widespread explanatory approach of a dichotomy with two poles: social and entrepreneurial. According to this, a lesser expression of one pole automatically leads to an approach toward the other pole. Social entrepreneurship is to be positioned in the middle of the two poles. On the basis of a qualitative empirical study (qualitative content analysis and metaphor analysis), this paper questions the basic understanding of the bipolar continuum and postulates a different, four-dimensional basic understanding of social entrepreneurship. This new draft does better justice to the given complexity of social entrepreneurship and provides an expanded explanatory approach to how social entrepreneurship can be conceptualized beyond the two dimensions. An approach with 36 types of social entrepreneurship emerges from the research results. The implications for science and practice are discussed. This article contributes to a better understanding of the different logics of social enterprises with hybrid organizational principles dedicated to sustainable development.
CRIS-Team Scopus Importer:2022-05-06
Keywords: bipolar; continuum; definition; dichotomy; hybridity; social enterprise; social entrepreneur